Pemeriksaan Kualitas Susu Asal Kedai Susu Kawasan Permukiman Mahasiswa IPB Dramaga dan Cilibende Bogor - Maharani -; Mirnawati B Sudarwanto; Susi Soviana; Herwin Pisestyani (JURNAL KAJIAN VETERINER, 2020)
Milk is an animal food source that plays a role in human life because it contains various nutritional components. Indonesia’s level of milk consumption is still relatively low. As one of an attempt to increase milk consumption, various kinds of processed milk products with a more modish aroma and form were made. However, not all of the quality of the processed milk products sold can be guaranteed. The aim of this study is to determine the quality of milk samples obtained from milk retails located around the students settlement area of IPB University’s Dramaga and Cilibende campus. The total of retails around campus obtained from the survey were 13, so 39 samples were bought. Milk samples taken were plain milk without an addition of sugar, flavor variants or ice cubes. The results obtained by the average value of density, content of fat, protein, lactose, dry matter, non-fat dry matter and pH of milk samples in Dramaga region are 1.0190 g/mL, 2.66%, 2.02%, 3.03%, 8.18%, 5.52% and 6.89. Milk samples in Cilibende region are 1.026 g/mL, 3.80%, 2.75%, 4.13%, 11.34%, 7.54% and 6.54. Based on pasteurization and sterilization perfectness test, it was discovered that all samples were pasteurized milk, even as much as 30.8% were sterilized milk. From this study, it can be concluded that the ready-to-drink milk sold in retails around the students settlements of IPB University has poor quality because it does not meet the minimum standard requirements of SNI No. 01-3951-1995 about Pasteurized Milk.